Relationship between hydrothermal fluids and microseismic activity on the south-east coast of Milos Island - ΜΠΑΛΤΑΤΖΗΣ, Ε.; ΔΕΛΗΜΠΑΣΗΣ, Ν.; VALSAMI-JONES, E.; ΠΥΡΛΗ, Μ.; BAIER, Β. (Bulletin of the Geological Society of Greece, 2001)
Milos island belongs to the Greek volcanic arc and is part of a small number of hot spots in the South Aegean Sea. It is an area that stands out for the diversity in volcanic formations and chemical composition of rocks. The island is characterized by the presence of a high enthalpy geothermal field and a non continuous microseismic activity, expressed both by tectonic earthquakes and swarm activity. During the period of our study (May-December 1999), this activity, which was recorded by a small, portable, seismological network has been very small and limited in the SE part of the island. From the chemical analyses performed, no significant alterations in the composition of the hydrothermal fluids was detected, except from slight changes in the content of K, Ca and Li and even smaller changes in Mg and Fe. This fact certainly implies a possible relation between microseismic activity and alterations in the content of various chemical elements, but it still needs further verification, which means that our research should be prolonged for a time period of at least two years